Development of E-Module Teaching Materials Based on Socio-Scientific Issues to Improve Students’ Science Literacy on The Global Warming Topic - Amalia Cahya Anggraheni; Ulfa Lutfianasari (Chemistry in Education, 2025)
Indonesian education has undergone a curriculum change in the form of the "Merdeka Curriculum," where one of the challenges faced is the limited availability of teaching materials, which affects the learning process of students. Another challenge Indonesia faces is the low level of scientific literacy among students. Therefore, it is necessary to develop teaching materials in the form of an e-module based on socio-scientific issues to improve students' scientific literacy. The purpose of this study is to determine the feasibility, student responses, and effectiveness of the e-module, as well as to analyze the improvement in students' scientific literacy. This type of research is Research and Development (R&D) using the 4D development model, namely define, design, develop, and disseminate, to produce a product that is suitable for use. The developed e-module was validated by five experts and achieved a high validity level (90.3% for content and 90% for media). Student responses to the e-module showed very good results, with an average score of 60.85 for class X-3 and 61.59 for class X-4. The N-gain test showed significant effectiveness, with a score of 0.735 (high category) for class X-3 and 0.677 (medium category) for class X-4. The results of this study indicate that the socio-scientific issue-based e-module is effective in improving students' scientific literacy on the topic of global warming.